All Days 2007
DOI: 10.2118/105066-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Delay Additive for Hydraulic Fracturing Fluids

Abstract: A new delay agent has been developed which has hybrid functionality versus previously-reported materials. It delays viscosity development in fracturing fluids based on guar derivatives crosslinked with a variety of common zirconate and titanate crosslinkers under a wide range of pH. The viscosity development can be optimized by adjusting the concentrations of polymer, crosslinker, and delay additive to give the desired profile for a given hydraulic fracturing application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In this case, the gel strength increases from code B to code D and then achieves the highest value of code G after a certain period. Obviously, the gelation time is 11 min which is suitable for frac jobs, , and the completion time of gelation is 37 min.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the gel strength increases from code B to code D and then achieves the highest value of code G after a certain period. Obviously, the gelation time is 11 min which is suitable for frac jobs, , and the completion time of gelation is 37 min.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since the pH of carbon dioxide was incompatible with borate cross-linked guar gum gels, transition metal cross-linked guar derivative fluids have been applied in low pH situations. , However, a major disadvantage of the low pH fracturing fluids is the uncontrollable gelation time. The cross-linking reaction proceeds very rapidly, and sometimes, gelation time delay dose not even occur at all. , The untimely viscosity development increases the pumping pressure. Moreover, transition metal cross-linked polymer fluids are shear-sensitive, from which leads to an irreversible loss of viscosity. , To overcome this shortcoming, several types of delay agents, also called ligands once they have been coordinated to the metal center, are introduced to retard the cross-linking process of guar derivatives with metal ions, such as polyhydroxy compounds, alpha hydroxy acids, and alkanolamines, or their hybrid. ,− Delay characteristics are related to the original bonds formed by the ligands .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing crosslinker chemistry Ainley et al 1993, Putzig and St. Clair 2007, Sun and Qu 2011, and Legemah et al 2013 Enhancing breaker chemistry Brannon 1994, Sarwar et al 2011, Gunawan et al 2012, and Patil et al 2013 Fracture fluid additives Bang et al 2008, andKim et al 2015 Foamed fluids Hutchins and Miller 2005, Gupta et al 2005, Chen et al 2005, Friehauf and Sharma 2009, and Gupta and Carman 2011 Viscoelastic surfactant systems Samuel et al 1999, Gomaa et al 2011, and Gomaa et al 2015 Polymer chemistry Cramer et al 2004, and Gomaa et al 2014Proppant Technology Brannon et al 2004 These improvements contributed incrementally toward the goal of attaining the maximum theoretical conductivity that can be achieved in a homogeneous proppant pack.…”
Section: Methods Literature Referencesmentioning
confidence: 99%
“…Normally, to control the rate of a cross-linking reaction under acidic conditions, Lewis basic ligands are used to complex with the transition metal and delay the release of metal ions. This method has been applied in many cases, and it was found that the ligand containing an alcoholic hydroxyl group performed the best because it generated the strongest coordination bonds. ,, In this paper, an organic zirconium complex was synthesized using l -lactate and ethylene glycol as the ligands to slow down the cross-linking rate with the CMHPG thickener. Then, to improve the rheological properties of zirconium cross-linked CMHPG acidic fracturing fluids, functionalized two-dimensional (2D) layered transition-metal dichalcogenide (TMD) nanosheets were introduced.…”
Section: Introductionmentioning
confidence: 99%